Sustainable Approach for Linz-Donawitz Slag Waste as a Replacement of Cement in Concrete: Mechanical, Microstructural, and Durability Properties - Richa Palod; S. V. Deo; G. D. Ramtekkar (Advances in Civil Engineering)
Linz-Donawitz (LD) slag, solid waste produced during steel manufacture in basic oxygen furnace, is difficult when it comes to handling and disposal and has very limited utilization. To increase its reusability, the suitability of supplanting cement with LD slag in concrete was examined. To study the impact of partially replacing cement with LD slag on strength, microstructure, and durability of concrete, more than 150 samples were cast. The test results reveal that the highest compressive and flexural strengths were attained at 20% LD slag replacement and, beyond that, the strength decreased. The hydration products detected by X-ray Diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) were calcium silicate hydrate (C-S-H), ettringite, and calcium aluminosilicate hydrate (C-A-S-H). The scanning electron microscope (SEM) images of binary cement concrete showed denser microstructure and lesser voids. The sulphuric acid resistance, electrical resistivity, and carbonation resistance tests done reveal that acceptable durability could be achieved when cement is replaced by LD slag. It is deduced that LD slag can be utilized in partially replacing cement to achieve the desired strength. This research gives another comprehension of simultaneously managing steel industry waste for sustainable development and contributing added advantages to the economy.